Steven Box: a "Realist of a Larger Reality" - Scott, David (Demystifying power, crime and social harm, 2023)
This Introduction situates Power, Crime and Mystification within the academic context of critical criminology which had emerged in the early 1970s, a movement that Steven Box himself had helped to kick start with the publication in 1971 of another seminal text, Deviance, Reality and Society. Power, Crime and Mystification was published in 1983, the profound, conjectural moment of Margaret Thatcher’s second general election victory representing what Stuart Hall called ‘the great moving right show’, and its consolidation and legitimation through what Hall termed ‘authoritarian populism’. The chapter considers this moment and the intellectual and political developments underpinning the book’s publication. Second, the chapter explores the substance of the book itself and the gauntlet it threw down not just to what Jock Young called ‘establishment criminology’, and to liberalism more generally, but also to the myopia in critical criminology itself, particularly with respect to feminist work which Box foregrounds in the book. Finally, the chapter analyses the relevance of Box’s work today, both for critical criminology and for the broader debates around the repressive and violent authoritarian, state power imposed into the lives of the poor and powerless while the rampant criminality of the powerful remains, as ever, unregulated and unpoliced. This, in turn, raises questions about democratic accountability and social justice which were central concerns of the book in 1983 and which remain key political issues in the twenty-first century in a social world deeply divided by the lacerating social divisions of social class, gender, ‘race’ sexuality, age and ability/disability.